2018
DOI: 10.1038/s41467-018-03217-9
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive cancer immunotherapy using DNA-demethylated T helper cells as antigen-presenting cells

Abstract: In cancer cells, cancer/testis (CT) antigens become epigenetically derepressed through DNA demethylation and constitute attractive targets for cancer immunotherapy. Here we report that activated CD4+ T helper cells treated with a DNA-demethylating agent express a broad repertoire of endogenous CT antigens and can be used as antigen-presenting cells to generate autologous cytotoxic T lymphocytes (CTLs) and natural killer cells. In vitro, activated CTLs induce HLA-restricted lysis of tumor cells of different his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…3C and S3C). Our results are consistent with the literature that small changes in the methylation following 5-AZA-dC treatment result in significant gene reexpression (36). One possible explanation for this phenomenon is that demethylation does not spread evenly in the cell population, and cells that undergo stronger demethylation contribute more to gene reexpression.…”
Section: Vs Bjabsupporting
confidence: 92%
“…3C and S3C). Our results are consistent with the literature that small changes in the methylation following 5-AZA-dC treatment result in significant gene reexpression (36). One possible explanation for this phenomenon is that demethylation does not spread evenly in the cell population, and cells that undergo stronger demethylation contribute more to gene reexpression.…”
Section: Vs Bjabsupporting
confidence: 92%
“…TAAs that have been shown to drive anticancer immunity, especially in the setting of therapeutic anticancer vaccination, 102 103 encompass: (1) tissue differentiation antigens such as CD19, CD20, premelanosome protein (PMEL, best known as gp100), and melan-A (MLANA, best known as MART-1), as well as (2) ectopically expressed proteins such as carcinoembryonic antigens (CEAs), cancer/testis antigens, as well as multiple members of the MAGE and SSX protein families. [104][105][106] Central tolerance against these antigens is leaky (implying that naïve T cell clone that express lowaffinity TCRs are available) and peripheral tolerance can be overcome in the context of robust adjuvanticity. [106][107][108] Thus, although TAAs are generally weaker at eliciting anticancer immunity as compared with TNAs, 109 they can be relevant for ICD-driven immunity in tumors with low TNA load.…”
Section: Sources Of Icd Antigenicitymentioning
confidence: 99%
“…Mast cells have the ability to facilitate tumor proliferation and invasion directly,and indirectly promote tumor proliferation and invasion by regulating tumor microenvironment [22], it may provide further evidence for Mast cells can be applied in the adjuvant treatment of mammary adenocarcinoma and melanoma [23]. Previous studies have shown that Th2 cells, T helper cells, and Mast cells may play key roles in the development and invasion of cancer [24][25][26][27], our studies show that these immune cells may play a role in gastric cancer.…”
Section: Discussionmentioning
confidence: 98%